PENGGUNAAN PHET SEBAGAI MEDIA INTERAKTIF PEMBELAJARAN IPA PADA KELAS IV SEKOLAH DASAR - Anjar Sulistiawati; Andi Prastowo (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2021)
This study aims to determine whether PhET can be used as interactive multimedia in science learning in elementary schools and to find out what materials can be integrated with PhET interactive multimedia in science material for grade IV elementary schools. This type of research is descriptive qualitative research with a library research approach. Literature review is a type of educational research conducted and focused on the study, assessment and discussion of literature, both classical and modern. Then the data obtained were analyzed through the stages of data collection, data reduction, data presentation, and drawing conclusions. Based on the research that has been done, it can be concluded that interactive multimedia PhET can be used in science learning in grade IV in elementary schools. Science material in grade IV SD that can be integrated with PhET media is KD 3.4 Connecting force with motion on events in the surrounding environment and KD 4.4 Presenting experimental results about the relationship between force and motion. Through PhET media students can simulate force, motion, and friction, so that students can get an idea of the relationship between force, motion, and friction.